Ink Sequence Effects on Color Gamut in Multicolor Lithographic Printing (International Journal of Scientific Research in Science and Technology, 2024)
This research investigates the impact of ink sequences and paper substrates on color reproduction in offset printing. Through experimentation and analysis, we demonstrate how altering the sequence of ink application influences color gamut. The variations in color gamut depend on the ink transfer capabilities. The MYCK order allows the most extensive color gamut for the investigated conditions. However, the effect is less observed on uncoated paper due to its high absorbency, resulting in minimal changes in ink transfer processes. Furthermore, our study highlights a substantial difference in color gamut between coated and uncoated paper, emphasizing the importance of considering paper substrate for achieving desired color reproduction. This research provides valuable insights for optimizing color fidelity in offset printing processes.